2019
DOI: 10.1155/2019/7690764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfated Polysaccharide from Undaria pinnatifida (SPUP) on Proliferation, Migration, and Apoptosis of Human Prostatic Cancer

Abstract: Objective. To observe the effect of sulfated polysaccharide from Undaria pinnatifida (SPUP) on proliferation, migration, and apoptosis of human prostatic cancer. Methods. DU145 human prostate cancer cells were cultured in vitro, and the proliferation activity both in the control group and the SPUP treatment groups (25, 50, 100, 200 μg/ml) was measured by CCK-8 assay. The wound healing assay was conducted to detect the cell migration. Cell apoptosis was measured by flow cytometry. The protein and mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…Furthermore, we showed using a wound healing/ scratch assay that the migration of 2D cultured KRAS-mutant human and murine LUAD cells decreased when cells were exposed to biomimetic sulfated GAGs. The findings are consistent with previous studies, which showed that native sulfated GAGs reduce the migratory abilities of cancerous cells [41,42].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, we showed using a wound healing/ scratch assay that the migration of 2D cultured KRAS-mutant human and murine LUAD cells decreased when cells were exposed to biomimetic sulfated GAGs. The findings are consistent with previous studies, which showed that native sulfated GAGs reduce the migratory abilities of cancerous cells [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…However, the isolation and purification of homogenous sulfated GAGs is complicated and expensive. Sulfated polysaccharides have previously shown anti-proliferative and anti-migratory effects on cancerous cells cultured in 2D, which is in agreement with our findings [41,42]. Alginate is a linear polysaccharide and has the same backbone as GAGs with hydroxyl groups that can be sulfated using different sulfating agents, such as SO 3 /pyridine and HClSO 3 acid formamide [27][28][29]31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Undaria pinnatifida polysaccharide (UPP) has various pharmacological activities, such as antioxidant, immunomodulatory, and antitumor [16][17][18]. The polysaccharide (UPP-2) with a molecular weight of 1035.52 kDa isolated from U. pinnatifida was able to significantly promote the proliferation and cytocytosis of RAW264.7 cells and upregulate the mRNA expression of iNOS, TNF-α, IL-6, and IL-1β, and increase the secretion of nitric oxide, TNF-α, and IL-6, showing immunomodulatory functions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Koh et al [17] found that fucoidan isolated from New Zealand U. pinnatifida can inhibit the activities of starch hydrolase α-amylase, α-glucosidase, and amyloglucosidase, showing anti-diabetic properties. In addition, U. pinnatifida polysaccharide (SPUP) was able to inhibit the proliferation and migration rate of DU145 cells, and the expression of apoptosis-related factors caspase-3, caspase-9, and Bax was upregulated in the SPUP-treated group, which exhibited antitumor activity in prostate cancer [18]. Sulfation modification of plant polysaccharides can enhance many biological activities of polysaccharides, such as antioxidant, anti-inflammatory, and immunomodulatory [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%